Wczesne zaburzenia czynnościowe i metaboliczne u dzieci z cukrzycą typu 1 i nefropatią cukrzycową - Burlaka, Ievgeniia; Maidannyk, Vitaliy (Pediatric Endocrinology Diabetes and Metabolism, 2021)
Type 1 diabetes (T1D) is mainly a disease of children and young adults. The onset of disease is associated with 3 classical symptoms: polydipsia, polyphagia, and polyuria. Hyperglycaemia is the main and primary metabolic disorder in T1D. One of the complications developing as a result of microangiopathy is diabetic nephropathy (DN). Additionally, diabetes remains the most common reason for progressing to end-stage renal disease (ESRD). The aim of the study was to evaluate the most initial metabolic and functional disorders in diabetic children and children with DN. The study involved 76 children with T1D and diabetic nephropathy (aged 3 to 17 years). The levels of ET-1 measured using ELISA assay and ratio of lipid oxidation measured spectrophotometrically. Main clinical parameters (blood pressure, glycaemia, albuminuria, creatininaemia, HbA1C, cholesterol levels) were measured using conventional methods available in Clinical Paediatric Hospital No. 6 (Kyiv, Ukraine). The glomerular filtration rate (GFR) was calculated using the Schwartz formula. Patterns of the BP changes, kidney function impairment, ET-level, and metabolic and functional disorders in children with T1D and DN were found.